On world history an anthology - Herder, Johann Gottfried (Armonk M.E. Sharpe, 1996)
Johann Gottfried Herder (1744-1803) was an influential German critic and philosopher, whose ideas included "cultural nationalism" - that every nation has its own personality and pattern of growth. This anthology contains excerpts from Herder's writings on world history and related topics.
Includes bibliographical references (p. 333-335) and index.
Keywords: Herder, Johann Gottfried, 1744-1803.